Separation of Cells From Plasma by Means of Ultrasonics - WŁOCH, Andrzej; CZYŻ, Henryka; JASINSKI, Tadeusz (Archives of Acoustics, 2019)
This paper presents an analysis of use of ultrasonic standing wave in cell separation from bodily fluids based on the example of erythrocyte separation from plasma. It describes movement of red blood cells in plasma under the influence of the acoustic field (whose forces result from interaction of red blood cells with plasma as the vibrating medium) and under the influence of resistance forces in Stokes’ and Oseen’s approximation. The general properties of solutions of the motion equation are given. The solutions for the parameters of the ultrasonic wave and blood cells which are interesting in terms of practical applications in medical diagnostics are discussed. Time constants of the cell transportation to the regions of stable equilibrium in the field of ultrasonic standing wave are estimated. The formulas which determine the time needed to obtain the assumed concentration increase in plasma in nodes and/or anti-nodes of the standing wave are derived.